Translation as a Part of School Curriculum in Learning English Language - Panda, Aditya Kumar (Universitas Negeri Semarang, 2018)
In India, the students, who are from mother-tongue medium schools, are well-acquainted with translation which has been a part in the language subjects. It has been an integral element of subject English and also for other language subjects like Hindi, Sanskrit at school. It has been used as an effective tool in learning English, though it has been in debate for the last decades for its use in some countries. This paper will discuss translation as a part of school curriculum in learning English, its limitation, challenges and current research on the same.